Heads will roll! Routes to effective trust repair in the aftermath of a CEO transgression - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2018)
CEO transgressions are a common storyline in today's business press. Such incidents result in the need to repair trust for both the CEO and the organisation that the CEO leads. Existing empirical research on trust repair has focused primarily on interpersonal trust, resulting in a body of knowledge that provides many insights to the errant CEO but few insights for those who aim to repair trust in the organisation. Since organisations also need to regain the trust of stakeholders after a CEO transgression, research on organisational trust repair is clearly warranted. Organisations have options for trust repair that are not available to individuals (e.g. dismissing the transgressor), these actions may be initiated by parties other than the culpable party (e.g. the Board of Directors), and the mechanisms underlying organisational versus interpersonal trust repair may differ. However, trust in CEOs and their associated organisations may also be intertwined since the CEO is the symbolic representative of the organisation. To better understand how organisations and CEOs can repair trust in the aftermath of a CEO transgression, we conduct a scenario experiment examining two tactics that are commonly used in practice: CEO dismissal, and CEO apology + penance. We also examine the proposed underlying mechanisms of perceived repentance and perceived disentitativity. Results indicate that both tactics can influence trust in the CEO as well as the organisation, and that perceived repentance and perceived disentitativity mediate the effects of Board responses on trust in the CEO but not on trust in the organisation.